Etika Beragama, Berpaham, dan Bermazhab dalam Perspektif Islam - Anggraini, Anggi; Harun, Hamzah; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Differences in religion, schools of thought, and legal schools (madhhab) are historical–theological realities inherent in the Islamic tradition. However, in contemporary socio-religious practice, these differences often undergo ethical distortions that lead to exclusivism, the delegitimization of other groups, and symbolic conflicts in the name of religious truth. This article aims to analyze the concept of ethics in religion, thought, and madhhab from an Islamic perspective using a normative–philosophical approach, and to affirm its relevance within plural Muslim societies, particularly in Indonesia. This study employs a qualitative method based on library research by analyzing primary sources (the Qur’an and Hadith) and secondary sources in the form of works by classical scholars and contemporary Islamic thinkers. The findings indicate that Islam normatively positions ethics as a fundamental foundation in responding to differences, as reflected in the principles of adab al-ikhtil?f (ethics of disagreement), tas?muh (tolerance), taw?zun (balance), ‘ad?lah (justice), and wasathiyyah (moderation). The novelty of this article lies in its normative–philosophical synthesis between classical Islamic ethical concepts and contemporary discourse on religious moderation, thereby framing adherence to a madhhab not merely as juridical loyalty, but as a moral–intellectual awareness aimed at preserving the common good (ma?la?ah) and social harmony.